Fishing for nutrient-competing antagonists for ginseng pathogen control via root biomass - Shengyuan Xiao; Si-Heng Zhu; Rongqiang Cao (MethodsX)
Phytopathogenic fungi are primarily responsible for destructive plant diseases that threaten food security. Biological control agents are generally based on their antibiotic characteristics. Nutrient competition is typical in microbes; however, the use of nutrient-competing antagonists for plant disease control remains underutilized. We found that ginseng root biomass selectively enriches soil pathogens and that biomass depletion prevents pathogen accumulation. We developed a method to capture specific ginseng root biomass-decomposing fungi from soils. We obtained three fungi via this method: one typical ginseng pathogen, Fusarium oxysporum, and two nonpathogenic fungi. These fungi do not display antibiosis to each other. However, nonpathogenic fungi significantly prevent ginseng root biomass-mediated accumulation of F. oxysporum. In addition, all three of these fungi inhibit the changes in the soil fungal community mediated by ginseng root biomass. To validate pathogen inhibition and community manipulation, we tested the effects of a commercial biomass-decomposing fungus, Aspergillus oryzae, on F. oxysporum accumulation and soil fungal community alteration after the addition of ginseng root mixture. The results support our conclusion that this method is simple and effective. Our results highlight an innovative application of nutrient-competing antagonists for plant disease control and a convenient protocol for screening for nutrient-competing antagonists.